Geography for A-level - Skinner, Malcolm; Abbiss, Paul; Banks, Philip; Fyfe, Helen; Whittaker, Ian (Hodder Education, 2021)
Cramming all new-case studies and 100s of new questions into one book, this new edition of our AQA A-level Geography student book will capture imaginations as it travels around the globe. This book has been written by our expert author team and structured to provide support for learners of all abilities. The book includes: · Activities and regular review questions to reinforce geographical knowledge and build up core geographical skills · Clear explanations to help students to grapple with tricky geographical concepts and grasp links between topics · Case studies from around the world to vividly demonstrate geographical theory in action · Exciting fieldwork projects that meet the fieldwork and investigation requirements · The most up-to-date theory of plate tectonics This student book is supported by digital resources on our new digital platform Boost, providing a seamless online and offline teaching experience.